Neem pesticides in rice potential and limitations - Soon, Lim Guan (International Rice Research Institute, 1994)
This publication reviews the status and prospects of pest control using neem in rice-based cropping systems in developing countries, with special emphasis on its potential and limitations in IPM programs. The ultimate value of any control method in IPM is how much the method contributes to increased farmer profit and sustained crop production, and protects health and the environment. Another requirement is the reliability of the method in achieving acceptable pest control.